Foreign banks as shock absorbers in the financial crisis? - Giorgia Barboni (National Bank of Belgium, 2017)
This paper finds that foreign banks can act as a buffer against negative credit supply shocks, in contexts where the domestic credit market is heavily hit by a country-specific adverse shock. A new dataset is constructed, which combines Belgian Credit Register data with firms and banks' balance sheets. After 2008, Belgian firms borrowing from domestic banks experienced a stronger credit contraction (minus 1.8 percentage points) than firms borrowing from foreign banks. Also, foreign banks "cherry-picked" new relationships with more profitable firms to a higher extent during the crisis, and turned down existing relationships more frequently than domestic banks. Results from this paper suggest that foreign banks can mitigate negative financial shocks in countries where domestic financial intermediaries unexpectedly experienced the consequences of the financial crisis to a higher extent.
Keywords: G21; G32; F34; 330; Foreign banks; Financial Crisis; Credit Supply